Effect of Use of Application Substrate EggsDifferent Against Seed Productivity (Hatching Rate) Angelfish Fish (Pterophyllum Scalare) - Nalom Santun Sihombing; Lucien Pahala Sitanggang (Berkala Perikanan Terubuk, 2021)
This study aims to determine the highest degree of spawning using different substrates in the spawningaquaria. This research was conducted at the Freshwater Research Institute for the Sibolga Fisheries HighSchool. This research was conducted from May to August 2020. The method used in this study was acompletely randomized design experimental method (CRD) with four treatments and three replications.The treatments are P0 (without using a substrate), P1 (Paralon Substrate), P2 (Ceramic Substrate), P3(Glass Substrate). The results showed that the best substrate for angelfish spawning was ceramic substratewith 840 eggs, 778 larvae hatching eggs, and the highest survival rate of 579.